2013
DOI: 10.1089/thy.2012.0579
|View full text |Cite
|
Sign up to set email alerts
|

The Extrathyronine Actions of Iodine as Antioxidant, Apoptotic, and Differentiation Factor in Various Tissues

Abstract: We propose that the International Council for the Control of Iodine Deficient Disorders recommend that iodine intake be increased to at least 3 mg/day of I2 in specific pathologies to obtain the potential extrathyroidal benefits described in the present review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 77 publications
4
68
1
3
Order By: Relevance
“…A number of reports have indicated that I 2 exerts antineoplastic effects in thyroid, mammary and prostate glands, all of which were shown to take up I 2 , whereas iodide supplementation had no effect (2,15,16). This is in line with the observation that I 2 treatment of patients with benign breast disease led to a bilateral reduction in breast size and a remission of disease symptoms, which was not observed when iodide was administered (17).…”
Section: Discussionsupporting
confidence: 56%
“…A number of reports have indicated that I 2 exerts antineoplastic effects in thyroid, mammary and prostate glands, all of which were shown to take up I 2 , whereas iodide supplementation had no effect (2,15,16). This is in line with the observation that I 2 treatment of patients with benign breast disease led to a bilateral reduction in breast size and a remission of disease symptoms, which was not observed when iodide was administered (17).…”
Section: Discussionsupporting
confidence: 56%
“…Previously, it has been reported the antioxidants effects of iodine [12,32,33], while in this study low doses of iodine (5 to 500 μM) decrease ROS levels. This data suggest that iodine may play a role in redox balance.…”
Section: Discussionmentioning
confidence: 48%
“…In the thyroid gland, intracellular iodine concentration plays an important role in redox balance by modulating hydrogen peroxide generation [8,9] and thyroid iodine deficiency induced intracellular production of reactive oxygen species (ROS) that stabilizes HIF-1α protein and then the expression and secretion of vascular epithelial growth factor (VEGF) for novel blood vessels [10]. It has been proposed that in thyroid and extrathyroid tissues, iodolipids are the mediators of iodine properties, through PPAR-gamma activation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of concentrating iodine in lactating mammary tissue is clearly to provide necessary iodine to the developing child. The role of iodine in most other tissues is believed to include antioxidant, anti-inflammatory, anti-proliferative, antibacterial, proapoptotic, and prodifferentiating effects [7]. Thyroid nodules are a common clinical problem.…”
Section: Introductionmentioning
confidence: 99%